Motivation for Participating in a Weight Loss Program and Financial Incentives: An Analysis from a Randomized Trial - Melissa M. Crane; Deborah F. Tate; Eric A. Finkelstein; Laura A. Linnan (Journal of Obesity)
This analysis investigated if changes in autonomous or controlled motivation for participation in a weight loss program differed between individuals offered a financial incentive for weight loss compared to individuals not offered an incentive. Additionally, the same relationships were tested among those who lost weight and either received or did not receive an incentive. This analysis used data from a year-long randomized worksite weight loss program that randomly assigned employees in each worksite to either a low-intensity weight loss program or the same program plus small financial incentives for weight loss ($5.00 per percentage of initial weight lost). There were no differences in changes between groups on motivation during the study, however, increases in autonomous motivation were consistently associated with greater weight losses. This suggests that the small incentives used in this program did not lead to increases in controlled motivation nor did they undermine autonomous motivation. Future studies are needed to evaluate the magnitude and timing of incentives to more fully understand the relationship between incentives and motivation.